Implementasi PBL Berbasis CRT melalui Konten Digital untuk Meningkatkan Hasil Belajar (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the implementation of the Problem-Based Learning (PBL) model combined with the Culturally Responsive Teaching (CRT) approach through the utilization of various forms of digital content to optimally enhance students’ learning outcomes. The research employs a descriptive qualitative design aimed at gaining an in-depth understanding of the learning process being implemented. The primary data were obtained from an analysis of the Grade VIII Indonesian language teaching module, while supporting data were collected through interviews with students of the Teacher Professional Education (PPG) program involved in the learning process. The findings indicate that the design and implementation of learning activities followed the stages of PBL systematically, thereby encouraging collaboration, active discussion, and problem-solving activities in the classroom. CRT principles were clearly reflected in the selection of learning materials related to students’ cultural backgrounds, such as speech texts representing Banjar and Javanese cultures. The integration of digital media, including Google Sites, instructional videos, and interactive quizzes, was proven to increase students’ engagement, motivation, and participation during the learning process. Overall, the synergy between PBL, CRT, and digital content created a more relevant, inclusive, and contextual learning environment and had a positive impact on improving students’ learning outcomes.